Targeting Myeloperoxidase (MPO) Mediated Oxidative Stress and Inflammation for Reducing Brain Ischemia Injury: Potential Application of Natural Compounds - Chen, Shuang; Chen, Hansen; Du, Qiaohui; Shen, Jiangang (Frontiers in Physiology, 2020)
Oxidative stress and inflammation are two critical pathological processes of cerebral ischemia-reperfusion injury. Myeloperoxidase (MPO) is a critical inflammatory enzyme and therapeutic target triggering both oxidative stress and neuroinflammation in the pathological process of cerebral ischemia-reperfusion injury. MPO is presented in infiltrated neutrophils, activated microglial cells, neurons, and astrocytes in ischemic brains. Activation of MPO can catalyze the reaction of chloride and H2O2 to produce HOCl. MPO also mediates oxidative stress by promoting the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS), modulating the polarization and inflammation-related signaling pathways in microglia and neutrophils. MPO can be a therapeutic target for attenuating oxidative damages and neuroinflammation in ischemic stroke. Targeting MPO with inhibitors or gene deficiency significantly reduced brain infarction and improved neurological outcomes. This article discusses the important roles of MPO in mediating oxidative stress and neuroinflammation during cerebral ischemia-reperfusion injury and review the current understanding of the underlying mechanisms. Furthermore, we summarize the active compounds from medicinal herbs with the potentials as MPO inhibitors for anti-oxidative stress and anti-inflammation to attenuate cerebral ischemia-reperfusion injury, and as adjunct therapeutic agents for extending the window for thrombolytic treatment. We highlight that targeting MPO could be a promising strategy for alleviating the ischemic brain injury, which merits further translational study.